Molecular Recognition: Multipoint Hydrogen Bonding‐Based Molecular Recognition of Amino Acids and Peptide Derivatives in a Porous Metal‐Macrocycle Framework: Residue‐Specificity, Diastereoselectivity, and Conformational Control (Small 22/2021). Issue 22 (2nd June 2021) - Tashiro, Shohei; Nakata, Kosuke; Hayashi, Ryunosuke; Shionoya, Mitsuhiko
Abstract : In article number 2005803, Shohei Tashiro, Mitsuhiko Shionoya, and co‐workers report residue‐specific recognition of amino acids and peptide derivatives in a porous metal‐macrocycle framework. Among several amino acid residues, serine moieties are site‐ and diastereo‐selectively adsorbed to a certain binding site on the pore surface through multipoint hydrogen bonding as clearly visualized by single‐crystal X‐ray diffraction analysis.